2018
DOI: 10.1007/s00423-018-1659-0
|View full text |Cite
|
Sign up to set email alerts
|

Is parathyroidectomy safe and effective in patients with normocalcemic primary hyperparathyroidism?

Abstract: In normocalcemic patients, parathyroidectomy is as safe and effective as in hypercalcemic patients. In the presence of symptoms and/or target organ disease, parathyroidectomy may have a positive effect on the outcome of NHPT patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 28 publications
2
37
0
Order By: Relevance
“…24 Lastly, in terms of the clinical presentation of normocalcaemic patients, the sensitivity of the imaging tests (mainly Tc-sestamibi scintigraphy and ultrasonography) was lower and was probably heavily influenced by the higher incidence of multiglandular disease and the presence of small adenomas, a finding shared by practically all series. 17,18,25,26 The main limitation of the present study is that there might be a selection bias, given that all patients were referred to surgery by the endocrinologist. However, in our centre the indications to send a normocalcaemic patient to surgery are similar to those of hypercalcaemic patients.…”
Section: Discussionmentioning
confidence: 96%
“…24 Lastly, in terms of the clinical presentation of normocalcaemic patients, the sensitivity of the imaging tests (mainly Tc-sestamibi scintigraphy and ultrasonography) was lower and was probably heavily influenced by the higher incidence of multiglandular disease and the presence of small adenomas, a finding shared by practically all series. 17,18,25,26 The main limitation of the present study is that there might be a selection bias, given that all patients were referred to surgery by the endocrinologist. However, in our centre the indications to send a normocalcaemic patient to surgery are similar to those of hypercalcaemic patients.…”
Section: Discussionmentioning
confidence: 96%
“…( 45 ) A large surgical single‐center retrospective study found that after parathyroidectomy, as many as 41.7% and 40.0% of patients showed improvements in BMD and kidney stones, respectively. ( 59 ) However, this study did not provide T ‐scores or BMD percentage changes.…”
Section: Surgical and Medical Outcomesmentioning
confidence: 89%
“…Whether parathyroidectomy improves renal outcomes in patients with normocalcaemic primary hyperparathyroidism remains much less understood. Traini et al followed a small cohort of patients (n = 10) and found that 40% of patients with pre‐existing nephrolithiasis no longer had stones after parathyroid surgery 59 . Another study of 48 patients with normocalcaemic primary hyperparathyroidism demonstrated an 80% cure rate in nephrolithiasis following removal of parathyroid adenomas and hyperplastic glands 61…”
Section: Managementmentioning
confidence: 99%